Clinical Determinants of Parents' Emotional Reactions to the Disclosure of a Diagnosis of Congenital Anomaly. Issue 2 (1st February 2013) - Fonseca, Ana; Nazaré, Bárbara; Canavarro, Maria Cristina
ABSTRACT Objective To examine parents' emotional reactions (high intensity vs. low intensity) and the intensity of each emotion when a prenatal or postnatal diagnosis of a congenital anomaly is disclosed Design Cross‐sectional study. Setting Two urban Portuguese hospitals. Participants The parents (60 mothers and 50 fathers) of 60 infants prenatally or postnatally diagnosed with a congenital anomaly. Methods One month after the disclosure of the diagnosis, the parents answered questionnaires regarding sociodemographic and clinical variables and their emotional experiences at the disclosure. Results Gender differences in the parents' emotional reactions were not found, and intracouple congruence was frequent. When there was uncertainty regarding the diagnosis, no prior knowledge about the diagnosis (for fathers only), and no history of pregnancy loss (for mothers only), parents presented significantly more frequently with a pattern of high‐intensity negative emotional reactions to the disclosure. Type of congenital anomaly, timing of diagnosis, and parity were not found to be significantly associated with the patterns of emotional reactions, but differences in the intensity of specific emotions were found for all variables. Conclusion Both parents' emotional experiences should be acknowledged at the disclosure. Clinical variables were found to define the stressful situation (the diagnosis). When the diagnosis was perceived as more threatening (i.e., more unexpected, less controllable, and predictable), parents presented a pattern of high‐intensity emotional reactions.